A Comprehensive Discussion in Vaginal Cancer Based on Mechanisms, Treatments, Risk Factors and Prevention - Baral, Sumit Kumar; Biswas, Partha; Kaium, Md. Abu; Islam, Md. Aminul; Dey, Dipta; Saber, Md Al; Rahaman, Tanjim Ishraq; M, A.; Emran, Talha Bin; Hasan, Md. Nazmul; Jeong, Mi-Kyung; Han, Ihn; et al. (Frontiers in Oncology, 2022)
Vaginal cancer is a rare and uncommon disease that is rarely discussed. Although vaginal cancer traditionally occurs in older postmenopausal women, the incidence of high-risk human papillomavirus (HPV)-induced cancers is increasing in younger women. Cervical cancer cells contain high-risk human papillomavirus (HPV) E6 and E7 proteins and inhibiting HPV gene expression leads the cells to stop proliferating and enter senescence. As E6, and E7 protein promoted the carcinogenesis mechanism, and here not only regulate the cellular degradation of P53, and pRb but also enhances the cell proliferation along with E6 protein targets the p53 for breakdown and subsequently promote the apoptotic cell death, and DNA repair inhibition, that is indispensable to the continue the lifecycle of the HPV. As a synchronous or metachronous tumor, vaginal cancer is frequently found in combination with cervical cancer. It is uncertain what causes invasive female vaginal organ cancer. HPV type 16 is the most often isolated HPV type in female vaginal organ cancers. Due to cancer's rarity, case studies have provided the majority of etiologic findings. Many findings demonstrate that ring pessaries, chronic vaginitis, sexual behavior, birth trauma, obesity, vaginal chemical exposure, and viruses are all risk factors. Because of insufficient understanding and disease findings, we are trying to find the disease's mechanism with the available data. We also address different risk factors, therapy at various stages, diagnosis, and management of vaginal cancer in this review.